Resection versus preservation of the middle turbinate in surgery for chronic rhinosinusitis with nasal polyposis: a randomized controlled trial - Marc-Antoine Hudon; Erin D. Wright; Etienne Fortin-Pellerin; Marie Bussieres (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Chronic rhinosinusitis (CRS) affects up to 16% of the population. When medical treatment fails, endoscopic sinus surgery (ESS) is considered. The value of resecting the middle turbinate to optimize surgical outcomes has been hypothesized but remains controversial and unproven. Whether the middle turbinate should be left in place or resected is controversial. Our objective is to determine if middle turbinectomy improves objective surgical outcomes after ESS. Methods Sixteen patients (15 men, 15 primary surgery) undergoing bilateral complete ESS for CRS with nasal polyposis were recruited. Nasal cavities were randomized so that middle turbinectomy was performed on one side while the middle turbinate was preserved on the other. Each participant acted as their own control. Nasal cavities were compared using Perioperative Sinus Endoscopy (POSE) and Lund-Kennedy (LKES) scores pre-operatively, and at 1, 3 and 6 months after ESS. Results were analyzed using Wilcoxon signed-rank test. Results Pre-operatively, the POSE (12.4 ± 2.9 vs 12.8 ± 2.6, p = 0.33, for the preserved side and the resected side, respectively) and LKES (5.0 ± 1.0 vs 4.8 ± 1.2, p = 0.33) scores were similar between sides. During follow up, resection was associated with more crusting at 1 month following ESS (1.0 ± 0.7 vs 0.4 ± 0.6, p = 0.02). There was a small, but statistically significant, difference between the nasal cavities at 3 months, where the resected side showed better endoscopic appearance (2.0 ± 2.2 vs 3.4 ± 2.8, p = 0.01). No difference was found at 6 months. Frontal sinus scores were similar between sides at 6 months (0.7 ± 0.5 vs 0.7 ± 0.5, p = 1.00). Conclusion Our results show no sustained objective endoscopic benefit of routine middle turbinectomy, at least within the first six postoperative months, in patients undergoing primary ESS for CRS with polyposis. Trial registration NCT, NCT02855931. Registered 16 August 2016.